Cortisol levels and perceived stress in emergency call operators - Kinga Kulczycka; Beata Chilimoniuk; Anna Rymuszka; Ewa Stychno; Agnieszka Bałanda-Bałdyga; Klaudia Pałucka (Frontiers in Public Health)
IntroductionEmergency medical dispatchers are required to provide support to the caller and organize help at the scene, frequently facing demanding situations where assistance decisions must be made promptly. The aim of this study is to assess the level of stress experienced by medical dispatchers and emergency call operators, in relation to their well-being and physical health symptoms.Materials and methodsA study was conducted in 2023 involving 23 healthy individuals employed as emergency medical dispatchers and emergency call operators, aged 26 to 65, from the Lublin Voivodeship. Data was collected based on continuous observation conducted over a 12-h day shift, utilizing the JAWS and VAS questionnaires and assessing every 2 h the following: salivary cortisol levels, heart rate, and blood pressure.ResultsThe employee’s level of arousal correlated with cortisol levels and significantly decreased during working hours, B = −13.87, SE = 5.16, p = 0.009. Among women, there was an increase in average heart rate during subsequent work hours, B = 47.4, SE = 22.0, p = 0.035. At the end of the workday, longer emergency caller interactions correlated with lower employee heart rates, B = −0.57, SE = 0.28, p = 0.046. Systolic blood pressure significantly increased with a rise in subjective stress assessment, but only during the first 2 h of work, B = 16.20, SE = 5.63, p = 0.005. Diastolic pressure depended on the employee group; among medical dispatchers, diastolic pressure values were higher at the beginning of the shift compared to the end, B = −40.2, SE = 23.9, p = 0.098, while an opposite trend with increased diastolic pressure was observed among 112 caLL operators.ConclusionThe cortisol profile is typical in the group of study participants. Attitude toward work correlates with physiological stress parameters. Longer conversations with an emergency caller during the final hours of work lead to a reduction in employees’ heart rates. Women exhibit an increase in heart rate as work progresses. Systolic blood pressure reflects subjective stress assessment during the first 2 h of work. Blood pressure values indicate a higher stress level in the 112 caLL operators group.